"Polish Comes from the Cities, Wisdom from the Desert": Stories and Manners in Late Antique Rabbinic and Monastic Literature - Briata, Ilaria (European journal of jewish studies, 2025)
The article explores late antique representations of ideal behavior and social interaction in rabbinic literature through a comparison with early Christian monastic traditions on religious etiquette. The study analyzes narratives on manners from Derekh Ereṣ Rabbah, a rabbinic tractate, in Hebrew, instructing on manners and morals (7th-10th cent.), and Apophthegmata patrum, a Greek anthology of sayings and stories attributed to the Egyptian desert fathers (5th-6th cent.). The stories, conveying a vivid depiction of their respective communities’ lifestyles, present similar stylistic features, ascribable to the Hellenistic genre of chreia, which was incorporated in both traditions. The narratives selected address the following themes: (1) fasting and hospitality; (2) the spoiled meal; (3) disgust, taste, and tact. The close reading, contrasting materials sharing stylistic format (chreia) and subject matter (etiquette), focuses on the literary, conceptual, and cultural dynamics of sociability, offering a phenomenological outlook on the rabbinic and monastic constructions of exemplary praxis beyond the notion of religious normativity.